Sourcing african ivory in chalcolithic Portugal - Schuhmacher, Thomas X. (2013)
A recent review of all ivory from excavations in Chalcolithic and Beaker period Iberia shows a marked coastal distribution – which strongly suggests that the material is being brought in by sea. Using microscopy and spectroscopy, the authors were able to distinguish ivories from extinct Pleistocene elephants, Asian elephants and, mostly, from African elephants of the savannah type. This all speaks of a lively ocean trade in the first half of the third millennium BC, between the Iberian Peninsula and the north-west of Africa and perhaps deeper still into the continent.